2009
DOI: 10.1108/02632770910980727
|View full text |Cite
|
Sign up to set email alerts
|

Successful IT implementation in facility management

Abstract: Purpose -The purpose of this research is a comparative analysis of computer-aided facilties management (CAFM) implementation projects and procedures in the German-speaking countries in order to derive appropriate implementation models. Since the 1990s CAFM has provided efficient information technology (IT) tools for mapping, evaluation and control of facility management (FM) structures and processes. Despite the multitude of vendors and users in different branches, there is still a lack of transparent and syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 2 publications
0
22
0
1
Order By: Relevance
“…Considerable research works have looked into FM in the last ten years, which are mainly concentrated on the following aspects: Innovation process for FM (Mudrak et al 2005;Sharma et al 2007;Lavy 2008;Madritsch and May 2009), measurement system for FM (De Toni et al 2007;Meng and Minogue 2011), Enduser requirements for green FM (Nousiainen and Junnila 2008), and improvement for FM (Lennerts et al 2005;Leung et al 2005;Pennanen et al 2005;Lavy 2008). From the literature review, three main disadvantages have been identified in the state-of-the-art FM:…”
Section: Bim and Fm Reviewmentioning
confidence: 99%
“…Considerable research works have looked into FM in the last ten years, which are mainly concentrated on the following aspects: Innovation process for FM (Mudrak et al 2005;Sharma et al 2007;Lavy 2008;Madritsch and May 2009), measurement system for FM (De Toni et al 2007;Meng and Minogue 2011), Enduser requirements for green FM (Nousiainen and Junnila 2008), and improvement for FM (Lennerts et al 2005;Leung et al 2005;Pennanen et al 2005;Lavy 2008). From the literature review, three main disadvantages have been identified in the state-of-the-art FM:…”
Section: Bim and Fm Reviewmentioning
confidence: 99%
“…Integrated Work Management Systems (IWMS) or Computerized Maintenance Management Systems (CMMS) support maintenance activities, work orders, space management, personnel management, etc. However, the exchange and re-usability of the data in these systems and the fragmented nature of AEC industry make the information transfer among project stakeholders challenging, especially through BIM [21].…”
Section: Bim In Facilities Maintenancementioning
confidence: 99%
“…In the European context, IWMS comes very close to the understanding of CAFM (Madritsch and May, 2009). However, the major difference is that CAFM mainly focuses on facilities management, space management and maintenance management while IWMS includes additional features like real estate and lease management, project management and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%